1994
DOI: 10.1111/j.1432-1033.1994.tb19070.x
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage oligomeric matrix protein and thrombospondin 1

Abstract: Cartilage oligomeric matrix protein (COMP) and thrombospondin 1 (TSP1) were purified in a native form from normal bovine articular cartilage. The key step in the purification scheme was selective extraction with EDTA‐containing buffer. Final separation of these two molecules was achieved by heparin affinity chromatography. Particles viewed by electron microscopy after rotary shadowing and negative staining revealed structures similar to their prototype molecules; from the Swarm rat chondrosarcoma for COMP, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
93
2
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(99 citation statements)
references
References 58 publications
2
93
2
2
Order By: Relevance
“…Attachment also depended upon the presence of calcium, since removal of calcium from thrombospondin 1 by treatment with EDTA completely inhibited the subsequent attachment of chondroeytes. A recent study [22] reported that bovine cartilage oligomeric protein (COMP) attached to articular cartilage chondrocytes, but that thrombospondin 1 did not. However, it should be noted that the thrombospondin 1 in that study was exposed to EDTA during its isolation, a procedure that irreversibly abolishes its capacity to attach chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Attachment also depended upon the presence of calcium, since removal of calcium from thrombospondin 1 by treatment with EDTA completely inhibited the subsequent attachment of chondroeytes. A recent study [22] reported that bovine cartilage oligomeric protein (COMP) attached to articular cartilage chondrocytes, but that thrombospondin 1 did not. However, it should be noted that the thrombospondin 1 in that study was exposed to EDTA during its isolation, a procedure that irreversibly abolishes its capacity to attach chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Unspecific binding sites were blocked with 1% bovine serum albumin. 5 ϫ 10 4 chondrocytes were incubated for 20 h at 37°C in substrate-coated wells as described earlier (37). Non-attached cells were removed by careful washing with phosphatebuffered saline.…”
Section: Methodsmentioning
confidence: 99%
“…We refer to the mutation here as deletion of Asp-470 because the net effect of deletion of any one of these 5 Asp residues is removal of the single Asp residue (Asp-470) that separates calcium-binding loops 10 and 11. , and recombinant proteins expressed in bacteria (C). The domain structure of a COMP monomer is based on primary sequence analysis of the thrombospondins, as well as electron microscopy (44), which shows a bouquetlike structure, topped with globular heads. Depiction of the various domains in not meant to infer specific structural conformations.…”
Section: Methodsmentioning
confidence: 99%